Cees Fasseur, Dubbelspoor. Herinneringen - Boudewijn J. Smits (BMGN: Low Countries Historical Review, 2017)
Cees Fasseur, Dubbelspoor. Herinneringen (Amsterdam: Balans, 2016, 368 pp., ISBN 978 946 003 117 5).